Meningkatkan Hasil Belajar Ekonomi Menggunakan Model Pembelajaran Kooperatif Tipe Jigsaw dengan Media Power Point pada Kelas X IPS-2 di SMA Negeri 2 Katingan Hilir Tahun Pelajaran 2016/2017 - Sinthya Ningsih; Aidin Najihi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
This study aims to 1) find out how the learning activities of students in the following learning using the Jigsaw Cooperative Learning Model with PowerPoint Media, 2) To determine whether there is an increase in economic learning outcomes in the subject matter of the market and market prices. After using the Jigsaw Type Cooperative Learning model with Media PowerPoint on students of class X IPS-2 Katingan Hilir 2 High School. This type of research is Class Action Research (CAR). The subjects of this study were students of class X IPS-2 in Katingan Hilir Lesson 2 High School 2016/2017 in the amount of 30 students. Data analysis is used in research qualitatively and quantitatively. Based on the results of the study, 1) Economic learning activities using the Jigsaw type learning model with powerpoint media in Katingan Hilir 2 High School. The operation of students in segment 1 obtained an average score of 3.18 into the category of being right. While in cycle two there is an improvement to be better, with an average rating of 3.91 good classes. 2) there is an economic improvement in learning outcomes with material on market issues and market prices by using the jigsaw cooperative learning model with powerpoint media in the X IPS-2 class of Katingan Hilir Public High School 2016/2017 academic year. This can be seen from the learning outcomes of students' data in the pre-action process of the pre-test period, getting an average value of 61 with classical mastery of 20.00% with criteria not reached, cycle 1 getting an average score of 69.5 with traditional knowledge, 67% with no tests achieved, and in the post-test 2 cycle the average rating was 81 with 100% classical mastery with the criteria fulfilled.